3-D modeling and molecular dynamics simulation of interleukin-22 from the So-iny mullet, Liza haematocheila - Qi, Zhitao; Shi, Rongwei; Li, Suyang; Zang, Xiayan; Wang, Zisheng (Electronic Journal of Biotechnology, 2013)
Background: Interleukin-22 (IL-22) plays an important role in the regulation of immune responses. However, little is known about its function or structure in fish. Results: The IL-22 gene was first cloned from So-iny mullet (Liza haematocheila), one of commercially important fish species in China. Then, 3-D structure model of the mullet IL-22 was constructed by comparative modeling method using human IL-22 (1M4R) as template, and a 5 ns molecular dynamics (MD) was studied. The open reading frame (ORF) of mullet IL-22 cDNA was 555 bp, encoding 184 amino acids. The mullet IL-22 shared higher identities with the other fish IL-22 homologs and possessed a conserved IL-10 signature motif at its C-terminal. The mullet IL-22 model possessed six conserved helix structure. PROCHECK, SAVES and Molprobity server analysis confirmed that this model threaded well with human IL-22. Strikingly, analysis with CastP, cons-PPISP server suggested that the cysteines in mullet IL-22 might not be involved in the forming of disulfide bond for structural stabilization, but related to protein-protein interactions. Conclusions: The structure of IL-22 in So-iny mullet (Liza haematocheila) was constructed using comparative modeling method which provide more information for studying the function of fish IL-22.